A Comparison of Administrative Data Versus Surveillance Data for Hospital-Associated Methicillin-Resistant Staphylococcus aureus Infections in Canadian Hospitals. (20th December 2016) - Ramirez Mendoza, Jessica Y.; Daneman, Nick; Elias, Mary N.; Amuah, Joseph E.; Bush, Kathryn; Couris, Chantal M.; Leeb, Kira
Abstract : BACKGROUND: In Canadian hospitals, clinical information is coded according to national coding standards and is routinely collected as administrative data. Administrative data may complement active surveillance programs by providing in-hospital MRSA infection data in a standardized and efficient manner, but only if infections are accurately captured. OBJECTIVE: To assess the accuracy of administrative data regarding in-hospital bloodstream infections (BSIs) and all-body-site infections due to MRSA. METHODS: A retrospective study of all (adult and pediatric) in-hospital MRSA infections was conducted by comparing administrative data against surveillance data from 217 acute Canadian hospitals (124 in Ontario, 93 in Alberta) over a 12-month period. Hospital-associated MRSA BSI cases in Ontario, and for all-body-site MRSA infections in Alberta were identified. Pearson correlation coefficients were used to compare the number of hospital-level MRSA cases within administrative versus surveillance datasets. The correlation of all-body-site MRSA infections versus MRSA BSIs was also assessed using the Ontario administrative data. RESULTS: Strong correlations between hospital-level MRSA cases in administrative and surveillance datasets were identified for Ontario (r=0.79; 95% CI, 0.72–0.85) and Alberta (r=0.92; 95% CI, 0.88–0.94). A strong correlation between all-body-site and bloodstream-only MRSA infection rates was identified across Ontario hospitals (r=0.95; P <.0001; 95% CI, 0.93–0.96). CONCLUSIONS: This study provides good evidence of the comparability of administrative and surveillance datasets in identifying in-hospital MRSA infections. With standard definitions, administrative data can provide estimates of in-hospital infections for monitoring and/or comparisons across hospitals. Infect Control Hosp Epidemiol 2017;38:436–443